L'étrangeté, l'exil et l'amour chez Beckett - Béryl Schlossman (Carnets)
The styles and subjects of Samuel Beckett's works continue to resonate in contemporary literature and theater: Beckett's modernity is contemporary with current 'post'-modern sensibility. Beckett's radical engagement with modernity is anchored in writing as the site of resisting any habits of subjective self- pity or complacency. A reading of First Love (first written in French, 1945) illustrates the ways that Beckett moves us beyond the predictable, into the strangeness of being and the poetic dimensions of language. From the rich play of language in the labyrinth of his early novels through the minimalism of his later years, fictional autobiography marks the unique history of his Nobel Prize awarded in 1969.